Percepção ambiental junto aos moradores do entorno do Arroio Tabuão no Bairro Esperança em panambi/RS - Nishijima, Toshio; Xavier, Cristiane de Lurdes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2010)
This study was conducted to investigate the perception of the residents of strean Tabuão in Neighborhood hope Esperança, RS in relation to the water quality of the stream Tabuão and itsimportance as a component of its surroundings; assess the level of information of respondents onenvironmental education and their interest in participating in this process, bringing the thought,the concepts of Environmental Awareness, landscape and environmental education. To achievethe proposed objective, bibliographic searches were carried out, as well as exploratory research toanalyze environmental perception of residents surrounding stream and the relationship with theenvironment in which they live. Were made interviews with residents of stream Tabuão. Theresults obtained allow to conclude that the environmental awareness of residents surroundingstream Tabuão is practically non-existent. The level of information and knowledge regardingenvironmental relations of interdependence is low. Relations of warmth and aesthetic value withthe stream Tabuão, are minimal or moderate and buried in the past.